Effects of varied aerobic exercise on health related outcomes of fibromyalgia patients: a randomized controlled trial - Abdeen, Heba A.; Bakry, Rufaida M.; El Nahas, Nesreen G.; Mohamed, Waleed A.; Hasanin, Marwa Esmael; Amin, Doaa I. (Zdorov'i︠a︡, sport, reabilitat︠s︡ii︠a, 2024)
Background and purpose Fibromyalgia (FM) is a chronic illness affecting the immune system. Women are more likely than men to be diagnosed with this condition. It causes widespread muscle and bone pain and is most commonly experienced by people between the ages of 20 and 60. Recent studies have shown that people with fibromyalgia may experience heart abnormalities and arrhythmias after exercise. This study explores how different aerobic exercise levels affect pain, cholesterol levels, and overall quality of life (QoL) for women with fibromyalgia. Materials and Methods In a study conducted at Abu-Kabir Central Hospital in Al Sharquia, 60 women diagnosed with fibromyalgia were randomly allocated to a moderate-intensity aerobic exercise (AE) (n=30) or a low-intensity aerobic exercise AE (n=30). The women were between the ages of 30 and 40 and had a body mass index (BMI) between 20 and 26 kg/m2. Before and after the intervention, all patients in both groups were evaluated using a visual analog scale (VAS), Fibromyalgia Impact Questionnaire (FIQ), symptom severity scale (SS-scale), and cholesterol level measurements. Results After the intervention, the group that engaged in moderate-intensity aerobic exercise showed significant improvements in all measured outcomes compared to the group that engaged in low-intensity aerobic exercise. The effect size was high for VAS (MD = -3.73; ES = 0.395 and p = 0.001), cholesterol level (MD = -52.19; ES = 0.681 and p = 0.001), FIQ (MD=-36.26; ES = 0.746 and p = 0.001), and symptom severity scale (MD = -473; ES = 0.273 and p = 0.001). Conclusion Our research has shown that moderate-intensity AE performed at 60% to 70% of maximum heart rate, is more effective in reducing pain, improving overall QoL, and lowering cholesterol levels than low-intensity AE at 45% to 55%.